Stakeholder interdependencies in a collaborative innovation project - Iqra Sadaf Khan; Osmo Kauppila; Noureen Fatima; Jukka Majava (Journal of Innovation and Entrepreneurship, 2022)
Industry 4.0 - also known as the modern industrial revolution-nurtures close collaboration between various organizations so that they can come together for innovation. While aiming for digital transformation through such innovation, these organizations form certain interdependencies due to the pool of resources and tasks they agree to share to reach both common and independent goals. To understand those interdependencies, we studied a national innovation project in Finland called "Reboot IoT Factory," which leveraged several resources, processes, and practices to successfully combine modern technologies in manufacturing in a competitive and sustainable way. The participants included in the project were factories, research organizations, and small and medium enterprises (SMEs). An actor dependency model was used to analyze the observed interdependencies through survey and interview data. The results showed strong goal, task, and resource dependencies between the participants. A conventional understanding of advantages and opportunities, such as increased experience sharing and possible long-term synergies, is elaborated; moreover, an analysis of the disadvantages and risks caused by interdependencies, such as delays in tasks and possible inefficiency through unnecessary complexity, is also conducted.
Keywords: 650; Actor dependency; Collaboration; Industry 4.0; Innovation; Interdependencies